Effects of Breast Feeding Practice in Respiratory Syncytial Virus Positive Bronchiolitis in Early Infancy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Bronchiolitis is a common respiratory illness. It can be diagnosed clinically, as well as by a few costly laboratory tests. It has no specific treatment except supportive measures. Respiratory Syncytial Virus (RSV) related Bronchiolitis carries near about 1% mortality and involve an economical load. The objective of this study was to compare effecte of breast feeding practice in relation with RSV positivity among bronchiolitis in early infancy.Material and methods: This case control study is designed to evaluate the effects of breast feeding practice among the RSV positive bronchiolitis patients during a period of 1 year. A total 40 patients of bronchiolitis were evaluated who have exclusive breast feeding and non exclusive breast feeding. RSV positivity were analyzed among both groups and compared. Patients were selected after taking consent from guardians, patient diagnosed as bronchiolitis, age 2 month to 2 year and all tests are done in Department of Microbiology, Chittagong Medical College Hospital (CMCH). Results were evaluated to find out the effects of breast feeding practice in relation with RSV positivity bronchiolitis in early infancy.Results: Among all 40 patients, male was 25(62.5%) and female was 15(37.5%). Male to female ratio was 1.67:1. Majority of guardians were workers 18(45%), service holder 11(27.5%) and businessman 10(25%). Regarding socioeconomic conditions of the parents where 26(65%) were poor and 14(35%) were rich. Twenty five (62.5%) were from rural areas and 15(37.5%) were from urban locality. Different history related with risk factors of bronchiolitis were evaluated where 11(27.5%) patients had H/O prematurity, 10(25%) had parental smoking history, nonexclusive breast feeding 13(32.5%) and supplemental feeding had 13(32.5%) cases. Regarding pattern of breast feeding 27(67.5%) were given exclusive breast feeding and non exclusive breast feeding were 13 (32.5%) of which only formula milk was given to 1(2.5%) case and cow’s milk and formula milk jointly was given in 12(30.0%) cases. Findings of clinical histories revealed that all 40 patients had cough, respiratory distress and excessive cry, cyanosis was present in 39(97.5%) cases and cent percent patients had chest in drawing and all of were categorized as severe bronchiolitis. Regarding RSV testing 15 (37.5%) cases were found to having RSV positive and remainder portion were negative. Significant association was found regarding RSV status and exclusive breast feeding where more negativity was found among those who were exclusively breast feed.Conclusion: There is significant association between RSV positivity bronchiolitis andnon- exclusively breast feed children.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 46-49